Spider monkey optimizations: application review and results - Abualigah, Laith (2024)
Optimization algorithms are applied to find efficient solutions in different problems in several fields such as the routing in wireless networks, cloud computing, big data, image processing and scheduling, and so forth. In this paper, we survey one of the metaheuristic algorithms: the spider monkey optimization (SMO). We present the algorithm procedure, discuss some of the recent related works and applications, and then highlight the strong and weak points of the SMO algorithm. This paper can assist in potential future research that involve use of the SMO.